SCIDOT-44. CREATING CAUSAL CAPABILITIES IN FUNCTIONAL BRAIN MAPPING USING A CED APPROACH. (11th November 2019) - Block, Walter; Birns, Rasmus; Olsen, Miles; Hurley, Samuel; Brodsky, Ethan; Rajala, Abigail; Filla, Caitlynn; McMillan, Alan; Alexander, Andrew; Jenison, Rick; Populin, Luis
Abstract: INTRODUCTION: The spatial and temporal resolution limits of functional MRI (fMRI) brain mapping provide primarily correlative information on brain connectivity. Determining how one region causally modulates and mediates activity in other regions remains difficult with fMRI. We demonstrate a simple means to add causality in resting state functional connectivity MRI (rs-fcMRI) using techniques developed first for convection-enhanced delivery (CED) of therapeutics. Here we use CED to guide and monitor pharmacologic alteration of a local brain region in anaesthetized Rhesus monkeys while monitoring rs-fcMRI signal changes. METHODS: Pre-surgical MRI was used to determine skull locations for craniotomies for installation of Navigus TM brain ports in two untrained monkeys slated for euthanasia. The ports were aligned in real–time to provide trajectories aimed at the central nucleus of the amygdala (CeA). Fused silica catheters were then inserted into the CeA where 24 mg of muscimol (inhibitory agent) was infused in 24 ml of buffered solution under pressure over 12 minutes, first on the right side and then on the left side. rs-fcMRI studies were done for 45 minutes before and after the unilateral infusion and then after the bilateral infusion. RESULTS: Catheters were successfully aligned and inserted into the CeA targets with sub-mm accuracy. T2-weighted imaging detected the enhanced T2 from the infusion's buffer. Pre-infusion rs-fcMRI provides results consistent with prior studies, which have shown that the CeA is most strongly connected to the contralateral CeA. This connectivity was significantly reduced following both unilateral and bilateral injections of muscimol into the CeA, demonstrating the effectiveness of the muscimol infusions. Conditional Grainger Causality (CGC) analysis shows unexpected new connectivity after the unilateral infusion. Upon the bilateral infusion, global effective connectivity in the region is reduced. CONCLUSION: Expected and unexpected changes in resting state functional connectivity resulted from unilateral and bilateral infusions of inhibitory agents.